The Implementation of Artificial Intelligence (AI) Technology and Students' Digital Literacy on Learning Outcomes in the Economics Learning Evaluation Course - Supriyadi Supriyadi; Ayu Nurul Amalia (Smart Society, 2026)
The rapid development of information technology requires students to possess adequate digital literacy skills to effectively access, evaluate, and utilize information in the learning process. At the same time, the implementation of Artificial Intelligence (AI) in education offers significant potential to enhance learning effectiveness, efficiency, and personalization. Therefore, it is important to examine how these two factors contribute to students’ academic achievement. This study aims to analyze the effect of AI implementation and digital literacy on students’ learning outcomes in the Learning Evaluation course. This research employs a quantitative method with a survey approach. The population of the study consists of 90 fifth-semester students from the Economic Education Study Program. A sample of 79 students was determined using the Isaac and Michael table at a 1% significance level, and selected through random sampling techniques. Data were collected using research instruments that had been tested for validity and reliability to ensure accuracy and consistency. The data were analyzed using partial regression and multiple regression techniques to examine both individual and simultaneous effects of the independent variables on the dependent variable. The results of the study reveal that: (1) the implementation of AI has a positive and significant effect on students’ learning outcomes; (2) digital literacy also has a positive and significant effect on learning outcomes; and (3) the implementation of AI and digital literacy simultaneously have a positive and significant effect on students’ learning outcomes. These findings indicate that both technological integration and students’ competencies in utilizing digital resources play crucial roles in improving academic performance. This study contributes by providing empirical evidence regarding the influence of AI implementation and digital literacy on student learning outcomes. The findings can serve as a reference for educators and institutions in designing effective learning strategies, improving the quality of higher education, and supporting the achievement of Sustainable Development Goal 4 (SDG 4), which emphasizes inclusive and quality education for all.